Analisis Determinan Tingkat Kemiskinan Di Indonesia - Marisa (PPJP ULM, 2019)
This research aimed to analyze the effect of economic growth, government expenditure, inflation, and unemployment on the level of poverty in Indonesia. This study uses time-series data in the form of annual data from the 1997-2017 period. This study's analysis technique uses the cointegration approach and Error Correction Model (ECM), and multiple linear regression models. The estimation results show that the variable of economic growth is statistically significant and negatively affects the level of poverty in Indonesia. Simultaneously, the variable of government expenditure, inflation, and unemployment are not statistically significant in influencing Indonesia's level of poverty. This study implies that economic growth is a macroeconomic variable that plays a significant role in reducing Indonesia's level of poverty.